If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -2) = 3x + -6 Reorder the terms: 8(-2 + x) = 3x + -6 (-2 * 8 + x * 8) = 3x + -6 (-16 + 8x) = 3x + -6 Reorder the terms: -16 + 8x = -6 + 3x Solving -16 + 8x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -16 + 8x + -3x = -6 + 3x + -3x Combine like terms: 8x + -3x = 5x -16 + 5x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 -16 + 5x = -6 + 0 -16 + 5x = -6 Add '16' to each side of the equation. -16 + 16 + 5x = -6 + 16 Combine like terms: -16 + 16 = 0 0 + 5x = -6 + 16 5x = -6 + 16 Combine like terms: -6 + 16 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| 2m-7=-8+m+1+3m | | 7(x-4)+10=2-3x | | 187-v=277 | | -2x+7x=-20 | | 3p+5p=72 | | 3+4x=36+3 | | X-(2x+1)=3-2(x+3) | | 12x-26=0x+4 | | x/12=-15 | | 69=-3(8a+1) | | -4(3x-1)=-20 | | 6x+4y+8z-4x+5z-7y= | | 6-8(1-7x)=-2-4x | | -4(3x-1)=-10 | | -1=5v+7-v | | -1=5v+7-v | | 11/23+11/23 | | 2x^3-9x^2+12x-4=0 | | 8/14-7/14 | | -139-9x=10x+21 | | -129-10x=132-31x | | -129-10x=132-31x | | 2y^2+26y+24=0 | | z^3-0.5*z+0.25=0 | | 85-5x=57-2 | | 0.2x+1.6=2 | | 12w^2+7w-10=0 | | 8/12*30/40 | | 46.00=4.00*m+2.00 | | 1.5(-4)+7.5= | | m*5+4=7 | | 4-(a+3)-13= |